2007
DOI: 10.1161/circresaha.107.149377
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 7 Silencing Alters Endothelial Cell Migration, a Key Step in Angiogenesis

Abstract: Abstract-Global inhibition of class I and II histone deacetylases (HDACs) impairs angiogenesis. Herein, we have undertaken the identification of the specific HDAC(s) with activity that is necessary for the development of blood vessels. Using small interfering RNAs, we observed that HDAC7 silencing in endothelial cells altered their morphology, their migration, and their capacity to form capillary tube-like structures in vitro but did not affect cell adhesion, proliferation, or apoptosis. Among several factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
140
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 48 publications
9
140
1
Order By: Relevance
“…These findings indicate that HDAC7 acts as a molecular switch to dynamically regulate VEGF signaling. The ability of HDAC7 to mediate VEGF signaling is consistent with recent studies showing that HDAC7 is critical for angiogenesis (19,20), a process in which VEGF plays a key role. We also found that other peptide growth factors, which complement or coordinate the actions of VEGF in regulating endothelial functions, also induce HDAC7 phosphorylation, albeit to a reduced level relative to VEGF.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings indicate that HDAC7 acts as a molecular switch to dynamically regulate VEGF signaling. The ability of HDAC7 to mediate VEGF signaling is consistent with recent studies showing that HDAC7 is critical for angiogenesis (19,20), a process in which VEGF plays a key role. We also found that other peptide growth factors, which complement or coordinate the actions of VEGF in regulating endothelial functions, also induce HDAC7 phosphorylation, albeit to a reduced level relative to VEGF.…”
Section: Discussionsupporting
confidence: 88%
“…HDAC5 and -9 function as stressresponsive inhibitors of cardiac growth (16,17), HDAC4 represses chondrocyte growth and differentiation (18), and HDAC7 maintains vascular integrity by repressing matrix metalloprotease 10 (MMP10) expression in ECs (19). A role for HDAC7 in modulating angiogenesis has also been suggested from in vitro assays (19,20). However, whether VEGF acts through HDAC7 to control angiogenesis and endothelial functions is unknown.…”
mentioning
confidence: 99%
“…The identification of cancer-related isoforms of HDAC has therapeutic interest in oncology as it might lead to the development of more specific and more efficient HDAC inhibitors with less toxicity and less side effects for patients. Using a small interfering RNA (siRNA) strategy, we have recently observed that specific silencing of HDAC7 led to a similar inhibition of angiogenesis to that observed with non-selective HDAC inhibitors suggesting that HDAC7 is probably the most relevant target(s) for inhibiting angiogenesis, one of the crucial step in cancer development (Mottet et al, 2007). Here, using a similar approach, we found that silencing of HDAC4 induces expression of p21 WAF1/Cip1 in various human cancer cell lines and decreases cancer cell proliferation in vitro and tumor growth in vivo, arguing perhaps that specific HDAC4 inhibitor could be also directly used as an effective chemotherapeutic molecule in cancer treatment.…”
Section: Hdac4 Represses P21waf1/cip1 Expression In Human Cancer Cellmentioning
confidence: 85%
“…Consistent with this, it has recently been reported that silencing of HDAC-7 also has profound effects on endothelial cells. Mottet et al (17) reported evidence of an altered migration of human umbilical vein endothelial cells (HUVECs) upon silencing of HDAC-7. They showed that this disturbance was at least partly due to an up-regulation of PDGF-B and PDGFR␤.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is almost undetectable in healthy skin, studies have revealed the increased presence of PDGF and PDGFRs in biopsy samples of SSc skin (16). According to Mottet et al (17), HDAC-7 silencing up-regulated the expression of PDGF-B and its receptor PDGFR␤ in endothelial cells. In order to examine whether gene knockdown of HDAC-7 alters the expression of PDGF-B and PDGFR␤ in SSc fibroblasts, we analyzed changes in the transcript expression levels of these genes in cells treated with HDAC-7 siRNA (n ϭ 6 each).…”
Section: Hdac-7 As a Target For Antifibrotic Therapy For Sscmentioning
confidence: 99%